(untitled) (Research, Society and Development, 2025)
The assessment of children’s nutritional status is an essential public health indicator, especially among indigenous populations, who have historically faced social, economic, and health vulnerabilities. The present study aims to analyze the nutritional status of indigenous children in the thirteen health regions of the State of Pará in 2024, based on data from the Food and Nutritional Surveillance System (SISVAN). The research, using a quantitative approach, utilized secondary information provided by the Ministry of Health, allowing the identification of malnutrition, adequate nutrition, and overweight rates among indigenous children. The results highlighted a situation marked by the double burden of malnutrition, with the coexistence of cases of undernutrition in more vulnerable regions, such as Tapajós and Lago de Tucuruí, and the increase in overweight in other areas, which may reflect the nutritional transition and the introduction of processed foods in the villages. These data can also be linked to social and territorial inequalities that compromise full child development and highlight the need for culturally sensitive intersectoral public policies. It is concluded that strengthening SISVAN and valuing traditional food knowledge are fundamental for promoting food security, health equity, and the sovereignty of the indigenous peoples of Pará.